2013
DOI: 10.4236/fns.2013.47a010
|View full text |Cite
|
Sign up to set email alerts
|

Biological Effect of Sucralose in Diabetic Rats

Abstract: Among people that might take a large amount of sucralose, are diabetic people who are attempting to modify their carbohydrate intake. The objective of this study is to evaluate the impact of sucralose; an artificial sweetener derived from sucrose, at a dose approximately twice the ADI on hyperglycemia, hyperlipidemia and oxidative stress in diabetic rats. Diabetes was induced in male albino rats after an intraperitoneal streptozotocin injection (65 mg/kg body weight). Animals with fasting blood glucose levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 52 publications
(48 reference statements)
1
8
0
Order By: Relevance
“…These hormones are peptides secreted by the enteroendocrine cells of the small intestine [ 42 ], are released in response to food intake, and have an important effect on the control of satiety and homeostasis of plasma glucose. In this work, Glucose Insulinotropic Peptide (GIP) was quantified for its metabolic function [ 43 , 44 ]. The results showed that sucralose reduces the secretion of GIP, glycaemia, and the HOMA index, but did not modify the insulin concentration; it also caused an increase in body weight with a reduction in feed intake, probably due to an increase in leptin secretion.…”
Section: Discussionmentioning
confidence: 99%
“…These hormones are peptides secreted by the enteroendocrine cells of the small intestine [ 42 ], are released in response to food intake, and have an important effect on the control of satiety and homeostasis of plasma glucose. In this work, Glucose Insulinotropic Peptide (GIP) was quantified for its metabolic function [ 43 , 44 ]. The results showed that sucralose reduces the secretion of GIP, glycaemia, and the HOMA index, but did not modify the insulin concentration; it also caused an increase in body weight with a reduction in feed intake, probably due to an increase in leptin secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is still unclear whether the consumption of NNS is helpful in the management of obesity and diabetes and related diseases. Some studies in healthy individuals and individuals with type 2 diabetes have demonstrated that sucralose does not affect appetite, glucose homeostasis, glucagon-like peptide-1 (GLP-1), and serum insulin (Brown, Brown, Onken, & Beitz, 2011;Ford et al, 2011;Grotz et al, 2003), while a review report and a study in diabetic rat suggest that sucralose consumption alters serum glucose, insulin, GLP-1 and lipid profile (Saada, Mekky, Eldawy, & Abdelaal, 2013;Schiffman & Rother, 2013). Studies conducted in mice suggested that NNS, including saccharine, aspartame, and sucralose induced glucose intolerance by altering gut microbiota (Suez et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Although several clinical studies have consistently suggested that both acute and chronic consumption of SU has no effects on insulin, GLP-1, glucagon, and glucose homeostasis, recent animal studies have reported contradictory results [ 26 , 27 , 28 ]. Saada et al [ 29 ] recently investigated the effects of SU administration in normal and STZ-diabetic rats at a daily dose of 11 mg kg −1 BW for six weeks. Their results indicated that SU administration reduces serum glucose and has no effects on serum insulin concentrations [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Saada et al [ 29 ] recently investigated the effects of SU administration in normal and STZ-diabetic rats at a daily dose of 11 mg kg −1 BW for six weeks. Their results indicated that SU administration reduces serum glucose and has no effects on serum insulin concentrations [ 29 ].…”
Section: Introductionmentioning
confidence: 99%